Electrical Recording of Effects of Chemotherapeutic Treatment on Cancer Spheroids - Ell, Maximilian; Bui, Mai Thu; Prado-Lopez, Sonia; Zeck, Gunther (Proceedings of IEEE Sensors ..., 2023)
Monitoring cells on substrates time-continuously without relying on optical microscopy imaging is of broad interest in biotechnological applications. We propose an approach to electrically investigate cytotoxic effects of a chemotherapeutic treatment on cancer cells using cell adhesion noise spectroscopy. Recordings are taken with high-density microelectrode arrays, data are analyzed in terms of spectral power density.